Identification and Robustness Analysis of Powertrain Excitation Forces - Xiao-ang Liu; Yechi Ma; Chunlei Jiang; Xiuxiu Sun (Shock and Vibration)
In order to get the excitation forces of the vehicle powertrain, a six-degree-of-freedom model of the powertrain mounting system is established. Two different identification methods are presented. Through the test of mount dynamic response, the powertrain excitations identified through these two methods are compared. The results show that the powertrain excitations identified through two methods are basically the same, since the mount accelerations at the body side are really small. The identified excitation is verified by comparing the deformation of torque strut. The robustness analysis of the mount acceleration phase affecting the identification results is also proposed. Improving the accuracy of phase in test input is helpful to improve the accuracy of identification results.